AN ABC BASED ACTIVE AND REACTIVE POWER ENHANCEMENT WITH OPTIMALLY DESIGNED DISTRIBUTED GENERATION AND DSTATCOM FOR 11KV YANTUKWANE NETWORK IN KADUNA, NIGERIA - ALABI, ISAAC I.; ABDULSALAM, YAHAYA S.; AIROBOMAN, ABEL E. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
In this paper the optimal placement of Distributed Generation (DG) and Distributed Static Compensator (DTATCOM) in the Yantukwane 11kkV feeder, Kaduna was carried out using Artificial Bee Colony (ABC) optimization Technique. The paper utilized the Loss Sensitivity Index (LSI) LSI and Load Flow Analysis (LFA) for identification of buses with higher losses. The proposed method was tested on the IEEE 33- bus radial distribution system, thereafter on the Yantukwane 11kV distribution network. The IEEE test results of the proposed method demonstrated better loss reduction and voltage profile improvement. The results from the Yantukwane network indicated a power loss reduction of approximately 64%. Also the minimum value of voltage magnitude without compensation was found to be 0.8432p.u, and after compensation the value become 0.9498p.u indicating the voltage profile improvement of approximately 11%. Thus, the study demonstrated the potential of Distributed Generation and Distribution Static Compensator to effectively reduce power loss and improve voltage profile in the radial distribution system.